2008
DOI: 10.3354/ame01214
|View full text |Cite
|
Sign up to set email alerts
|

Exopolymer particles: microbial hotspots of enhanced bacterial activity in Arctic fast ice (Chukchi Sea)

Abstract: Sea ice is an important structuring element of Arctic marine ecosystems and provides a vast low-temperature habitat for ice-associated bacteria. While it is now known that sea ice sequesters large amounts of extracellular polymeric substances (EPS) contributing significantly to its particulate organic carbon pool, the ecological role of EPS in sea ice is poorly understood. Using in situ incubations combined with a newly developed triple-staining method (Alcian Blue, DAPI, CTC), we determined the number of CTC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 72 publications
2
46
0
Order By: Relevance
“…One possible mechanism to account for the differential temperature response in our experimental microcosms is the change in solute concentrations in the remaining liquid water surrounding the soil particles that occur with decreasing temperatures. Increases in both the production of extracellular polymeric substances (acting as cryoprotectants) and in bacterial abundance under similar subzero temperature conditions have been observed in brine channels from sea ice and frost flowers (Krembs et al, 2002;Collins et al, 2008;Meiners et al, 2008;Bowman and Deming 2010;Krembs et al, 2011). This hypothesis is further supported by recent evidence that permafrost isolates have thermohaline-dependent responses for both polysaccharide and fatty acid composition (Ponder et al, 2005) as well as for gene expression patterns (Mykytczuk et al, 2013).…”
Section: Discussionsupporting
confidence: 68%
“…One possible mechanism to account for the differential temperature response in our experimental microcosms is the change in solute concentrations in the remaining liquid water surrounding the soil particles that occur with decreasing temperatures. Increases in both the production of extracellular polymeric substances (acting as cryoprotectants) and in bacterial abundance under similar subzero temperature conditions have been observed in brine channels from sea ice and frost flowers (Krembs et al, 2002;Collins et al, 2008;Meiners et al, 2008;Bowman and Deming 2010;Krembs et al, 2011). This hypothesis is further supported by recent evidence that permafrost isolates have thermohaline-dependent responses for both polysaccharide and fatty acid composition (Ponder et al, 2005) as well as for gene expression patterns (Mykytczuk et al, 2013).…”
Section: Discussionsupporting
confidence: 68%
“…Tedesco et al [2010], using a more advanced biogeochemical component (two algal species, varying nutrient quotas in algal cells), showed that so-called survivors, i.e., single algal cells surviving adverse environmental conditions, can significantly contribute to ice algal production. Furthermore, no model at this stage includes organic matter, while organic matter storage in sea ice is quite large, with important consequences for nutrient remineralization [Meiners et al, 2008]. Finally, a 1D representation of gas dynamics in sea ice has been applied to Ar, underlining the important role of bubbles [Moreau et al, in revision], but has not yet been applied to other climatically significant biogases.…”
Section: Modelling and Up-scaling The Role Of Sea Ice In The Marine Bmentioning
confidence: 99%
“…When sea ice melts, its dissolved and particulate constituents are released into the surface waters (27, 28), contributing to the microbial dynamics in both the melting ice and melt waters (19,(29)(30)(31). Physical aggregation of EPS in seawater to form larger particles may promote the sinking of particulate organic matter from the surface waters (19, 32), or produce EPS foams that are Significance Many marine microalgae and bacteria secrete polysaccharide gels (exopolymers) in response to environmental stresses, such as the freezing temperatures and salt concentrations that organisms experience when in sea ice.…”
Section: S Ea Ice Covers Extensive Regions Of the Arctic And Southernmentioning
confidence: 99%
“…When sea ice melts, its dissolved and particulate constituents are released into the surface waters (27,28), contributing to the microbial dynamics in both the melting ice and melt waters (19,(29)(30)(31). Physical aggregation of EPS in seawater to form larger particles may promote the sinking of particulate organic matter from the surface waters (19,32), or produce EPS foams that are…”
mentioning
confidence: 99%
See 1 more Smart Citation